Engaging students in seagrass-focused activities. (8th October 2020) - Roth, Jamila; Reynolds, Laura K.
Abstract: Seagrass ecosystems are widespread, valuable, and threatened. We have used this system as a model to teach 3 rd – 7 th grade students about food webs, the interconnectedness of ecosystems, ecosystem services, and the effects of human activity on coastal systems. Our objective was to increase student understanding of seagrass ecosystems and other key topics linked to Next Generation Science Standards in order to foster positive attitudes regarding science and highlight the importance of marine conservation. We delivered a 45-minute seagrass-focused lesson at four different afterschool science clubs ( n  = 47 students), including a short presentation with a live sea urchin and additional hands-on activities. Students learned how to create a seagrass food web and described how organisms are connected in an ecosystem. Surveys were given to students both before and after the lesson, and the proportion of correct responses on surveys increased after students participated in the lesson. Specifically, students demonstrated improved understanding of ecosystem services, a concept directly related to marine conservation, as well as improved understanding of the different roles in a food web. Students also demonstrated positive attitudes toward science, as 82% of students reported either "liking" or "loving" the activities.